Risk Management in Small and Medium Enterprises - Zhang, Yinzi (2011)
This research focuses on risk management in small and medium-sized enterprises (SMEs) of the UK. In particular, it seeks to explore the impact of personal and organizational characteristics on entrepreneurs' attitudes to risk and firms‟ risk management practices. Additionally, why some owner managers in SMEs more than others are more risk averse or adopt more risk management practices will be investigated in relation to business threats and objectives. Using the data collected by You Gov PLC in 2009, this study found that set up ownership, owner managers‟ age, firm size, industry sectors, and business threats or objectives have close relationship with risk taking attitudes and behaviours. Gender, which used to be significant in most of previous studies, is insignificant in our research. Besides, we cannot found the correlation between business location and risk taking attitudes and behaviours either.